Decreased parvalbumin and somatostatin neurons in medial prefrontal cortex in BRINP1-KO mice. (14th September 2018) - Kobayashi, Miwako; Hayashi, Yuichi; Fujimoto, Yuko; Matsuoka, Ichiro
Highlights: Decreased PV-expressing GABA neurons was observed in mPFC of BRINP1-KO mice. Decreased SST-expressing GABA neurons was observed in mPFC of BRINP1-KO mice. Possible involvement of cortical inhibitory neuron dysfunction in abnormal behavior of BRINP1-KO mice was discussed. Abstract: BRINPs (B MP/R A-i nducible N eural Specific P rotein-1, 2, 3) are family genes expressed mainly in both the central and peripheral nervous system. BRINP1 is abundantly expressed in many of adult brain regions including cerebral cortex and hippocampus, with expression regulated in an activity-dependent manner in the dentate gyrus. Mice with disrupted BRINP1 gene exhibit abnormal behaviors such as increased locomotive activity and poor social activity which are analogous to symptoms of human psychiatric disorders such as schizophrenia (SCZ), autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD). In the present study, to clarify the physiological roles of BRINP1 in psychiatric disorders, we examined the numbers of parvalbumin (PV)-expressing neurons and somatostatin (SST)-expressing neurons in the medial prefrontal cortex (mPFC) in BRINP1-KO mice. Immunohistochemical analysis revealed the numbers of PV-expressing neurons and SST-expressing neurons in mPFC of BRINP1-KO mice were, respectively, 50% and 20% fewer than corresponding neurons in mPFC of wild-type mice. These data suggest that the abnormal behaviors related to human psychiatric disorders in BRINP1-KO mice could be derived from the hyperexcitability of pyramidal neurons as a consequence of decreased inhibitory innervation and conceivable dysregulation of the Excitatory/Inhibitory balance in mPFC.